A retrospective study on the etiological diagnoses of diarrhea in neonatal piglets in Ontario, Canada, between 2001 and 2010 - Chan, Gloria (Canadian Veterinary Medical Association, 2013)
Laboratory surveillance data from the Animal Health Laboratory, University of Guelph, on the etiological diagnoses of neonatal diarrhea in piglets were analyzed to determine the relative importance and trends of different enteric pathogens in Ontario. A total of 237 cases, including live and dead 1- to 7-day-old piglets, were submitted for diagnosis of gastrointestinal illness between 2001 and 2010. The combined frequencies for cases of gastrointestinal illness involving Escherichia coli, Clostridium perfringens type A, rotavirus, and Clostridium difficile, either as single pathogens or a complex of pathogens, accounted for 56% of the total cases. In a total of 33% of cases of gastrointestinal illness, an etiological agent was not identified. The frequency of cases diagnosed with enterotoxigenic E. coli was decreased from 2007. Cases submitted in 2010 were more likely to be diagnosed with C. perfringens type A compared to cases submitted in 2002 to 2007 (P < 0.05). There was a significant trend for cases submitted in the winter to be diagnosed with C. perfringens type A, enterotoxigenic E. coli, rotavirus, and Cystoisospora suis (formerly Isospora suis) (P < 0.05). Enterotoxigenic E. coli was less likely diagnosed if C. difficile, C. perfringens, or rotavirus were detected (P < 0.05). Younger piglets were more likely to be diagnosed with C. perfringens type A (P < 0.05) and C. difficile (P < 0.05) than older piglets. This study shows that E. coli, C. perfringens type A, rotavirus, and C. difficile are enteric pathogens of concern for Ontario swine farrowing operations and further research is required to understand the reasons for the cases that are not diagnosed.